Persetujuan Pembangunan di Daerah Jalur Hijau di Dusun Gubug Belodan Kabupaten Tabanan - I Kadek Tedo Tamara Putra Daniswara; Ida Ayu Putu Widiati; Putu Ayu Sriasih Wesna (Fakultas Hukum Universitas Warmadewa, 2024)
Gubug Belodan Village is located in the scope of the Tabanan Regency area with a strategic location on the edge of the city, has a high lure to be used as a residential or commercial area which certainly greatly affects the agricultural land in Gubug Belodan Hamlet where the land used is finally in a shifting condition. Based on this, how is the granting of building approval (PBG) in the green belt area? And how is the policy of granting building approval (PBG) in the green belt of Gubug Belodan Hamlet, Tabanan Regency? This research uses empirical legal research. The green line, which is a public infrastructure and facilities, the establishment of buildings on the green line must have PBG based on Law No. 28/2002 on Building. Regarding the green belt development policy, it is also explained in the Tabanan Regency Regional Regulation No. 6/2014 concerning the Green Belt Area which provides an understanding that the establishment of buildings is not allowed permanently or not which is contrary to the functional and use of the defense area concerned in the green belt area, except with the permission of the Regent with the recommendation of the DPRD.